Underwater Invisible Light Communication Network with Beam Steering Technology for Dynamic Switching Between Aerial and Underwater Optical Paths - Kiichiro Kuwahara; Keita Tanaka; Ayumu Kariya; Shogo Hayashida; Takahiro Kodama (Sensors)
This study proposes a bidirectional underwater optical wireless communication network that maximizes data transmission capacity by dynamically switching between underwater and aerial optical paths based on channel conditions. The proposed system employs adaptive modulation and beam steering techniques to address dynamic factors, such as turbidity and transmission distance, in underwater channels. The experimental results revealed that switching to the aerial optical path when the underwater transmission distance exceeded 1.8 m led to significant performance improvements, with consistent SNR and bit rates maintained in the aerial channel, unlike the exponential degradation observed underwater. Dynamic evaluations demonstrated that the system maintained high transmission capacity and SNR stability, even with incremental increases in underwater distances. In a 4K UHD video streaming experiment, switching from the underwater optical path to the aerial path reduced video quality degradation, delivering near-original video quality with latency as low as 20 ms. Furthermore, tolerance experiments for beam steering misalignment showed a sharp performance drop at a maximum misalignment of 2 degrees, with a 12 dB SNR loss and a reduction of 222 Mbps in transmission capacity. These findings suggest that selectively utilizing underwater and aerial optical paths based on channel conditions enables reliable and efficient data transmission, paving the way for next-generation underwater optical wireless communication networks.